Design of a Personal Mobility Device for Elderly Users - Natthanon Phannil; Chaiyan Jettanasen (My University, 2021)
The ageing society has resulted in imbalances in the population age ratio. The ratio of working-age people was less than that of elderly people resulting in a shortage of elderly caregivers and increased healthcare costs. Although the lifestyle the elderly remains the same, their physical abilities are reduced, requiring them to rely on special equipment when traveling in order to gain more control and safety. Therefore, the Elderly Personal Mobility Device (EPMD) is developed using Internet of Things (IoT) technology to reduce the burden of caregivers, provide freedom and safety for elderly travelers, assess air pollution risks, and alert the occurrence of emergency events. The EPMD is designed in terms of structure, electrical equipment, and sensor systems. First, the shapes, sizes, and thicknesses of the carbon steel used for construction of the EPMD structure are calculated by using SolidWorks software. Next, the electric equipment is carefully selected to meet the requirements of actual use. Finally, the sensor system is designed to monitor the EPMD status and air quality using IoT devices to create a data interface and big data for elderly health service development, as well as an air quality map with distributed measuring stations and a charging station detection system for future use.
Keywords: Population Ageing; Economic shortage; Interface (matter); Transportation and Mobility Innovations